Lyme Disease in Florida Horses - Cynthia C. Lord; C. Roxanne Rutledge-Connelly (EDIS)
Lyme disease does affect horses, but is relatively unstudied compared to the disease in humans and dogs. It often presents as lameness, but other symptoms can occur. This document is ENY-711, one of a series of the Entomology & Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published: July 2004.